"MYH9 mutation and squamous cell cancer of the tongue in a young adult: a novel case report" - Takako Eva Yabe; Kylie King; Susan Russell; Laveniya Satgunaseelan; Ruta Gupta; James Chen; Bruce Ashford (BMC, 2022)
Abstract Background The incidence of tongue cancer in young adults is on the rise. This trend is more pronounced in females. Although the aetiology is still unclear, there is mounting evidence that genetic syndromes can play a key role in development of oral cancers in this patient group. We report the first case of oral squamous cell carcinoma (oSCC) in a young adult with an MYH9-related disorder (MYH9-RD). Case presentation A 19-year-old female with a germline MYH9 variant (missense variant in exon 2: c.287C > T, (p.Ser96Leu)) was referred to the head and neck surgery department for investigation of a painful, thick right tongue ulcer. She was diagnosed with Epstein syndrome, an MYH9-RD, at 12 years of age. Her main phenotypic features were profound thrombocytopenia and marked renal impairment. The tongue biopsy confirmed SCC. Preoperative positron emission tomography (PET) revealed avidity in the right tongue and ipsilateral level 2A neck lymph node. With substantial preoperative multidisciplinary input, she underwent cancer ablation and microvascular free flap reconstruction. Her pathology showed a 35 mm diameter, 14 mm thick moderately differentiated SCC with perineural and lymphovascular invasion. Two out of 38 right neck nodes were positive for metastasis with extranodal extension. None of the 34 left neck nodes was involved. She had an uneventful recovery and was discharged home on day 6 postoperative day. On day 15 postoperative day, she had catastrophic bleeding in the neck with a respiratory arrest after a forceful cough. She required an emergency tracheostomy and returned to the theatre for haemostasis. Following a short inpatient stay, she was again discharged home and underwent adjuvant therapy consisting of external beam radiotherapy of 60Gy in 30 fractions. On clinical examination and PET at 6 months after surgery, she had no evidence of disease recurrence. Conclusions MYH9-RD can present with advanced locoregional oral cavity malignancy at an early age. The combination of profound thrombocytopenia and marked renal impairment can impact heavily on routine major head and neck cancer surgery and adjuvant treatment. This rare and challenging condition underlines the importance of early detection of cancer and multidisciplinary team input.